Development of multi-objective optimization for high recyclability material selection in product design / Novita Sakundarini - Novita , Sakundarini (2013)
This thesis presents the development of a multi-objective optimization for high recyclability material selection in product design. The aim of the research is to build up methodology that aid designers to improve product’s recyclability that meet environmental legislative requirements. The research is motivated by low attention given on the high recyclability material selection in the literature review. There is also lack of study that developing an integrated method of recyclability assessment with material selection in product design specifically during conceptual design stage. The research was conducted in three phases: the survey, exploratory study and the multi objective optimization for high recyclability material selection. The survey was done by distributing an open ended questionnaire to the designers to reveal the current practice of how a designer incorporates environmental issues into product design. The exploratory study was performed by conducting interviews to seek designer’s existing practice specific for design of recycling and to determine what factors that significantly contribute to recyclability. The recyclability assessment using Fuzzy Inference System was employed in the High Recyclability Material Selection optimization model to minimize product’s weight, as well as maximizing its function and recyclability. Results from the survey showed that the awareness among designers in Malaysia to incorporate environmental concerns into the product design process were quite high but not properly implemented because lack of knowledge and management support. Five recyclability factors based on the recyclers’ current practices have been identified from the exploratory study, namely profit, recycling infrastructure, material separation, material combination and joining type. The proposed method may support the product’s recyclability which concurrently done during conceptual design stage. It is also resulted to an optimized set of design configurations that consider lightweight, functionality and recyclability. The report listed the significant factors that mostly influence product’s recyclability in Malaysia. The research also provided a new methodology to assist designers in incorporating recyclability aspect during product design.